2021
DOI: 10.1111/aos.15012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefits and potential risks of adalimumab in non‐JIA chronic paediatric uveitis

Abstract: Purpose To describe the treatment results with adalimumab in chronic paediatric uveitis, not associated with juvenile idiopathic arthritis (JIA). Methods Medical records of children with non‐JIA‐uveitis were reviewed retrospectively. Children without an underlying systemic disease were pre‐screened with brain magnetic resonance imaging (MRI) to exclude white matter abnormalities/demyelination. Results Twenty‐six patients were pre‐screened with brain MRI, of whom adalimumab was contraindicated in six patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…Our study demonstrated that ADA was effective in children with chronic posterior uveitis and panuveitis, with 90.6% attaining remission after 3 months, which was consistent with previous studies [ 3 , 21 ] including anterior uveitis cases. In our study, 46 eyes achieved symptom alleviation without relapse during follow-up.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study demonstrated that ADA was effective in children with chronic posterior uveitis and panuveitis, with 90.6% attaining remission after 3 months, which was consistent with previous studies [ 3 , 21 ] including anterior uveitis cases. In our study, 46 eyes achieved symptom alleviation without relapse during follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…The rates of achievement of the inactive state and success were 23.3% and 46.5%, respectively, during 1 year of treatment with ADA or infliximab. Kouwenberg et al [ 3 ] demonstrated that treatment with ADA led to prompt inactivity of non-JIA uveitis in the majority of children (90.6%), whereas this study included 15 (35%) and eight (18.6%) patients with anterior and intermediate uveitis, respectively. Another study that included the largest number of panuveitis cases (28 patients, 90%) demonstrated that anterior and posterior inflammation reached inactivity after 4 weeks in all cases [ 21 ].…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations